USE OF SEAWEED SAP FOR SUSTAINABLE PRODUCTIVITY OF MAIZE - SHIKHA SINGH; M. K. SINGH; S. K. PAL; R.THAKUR; S. T. ZODAPE; ARUP GHOSH (The Bioscan, 2015)
A field experiment was conducted at Birsa Agricultural University, Ranchi , during rainy season of 2012-13 and 2013-14 with maize variety HQPM-1 in randomized block design and replicated thrice, with two sources of seaweed sap Kappaphycus alvarezii (K sap) and Gracilaria edulis (G sap) at 6 concentrations (0.0, 2.5,5.0, 7.5,10.0 and 15.0%) with RDF (150:60:40 kg N:P2O5:K2O ha-1) and 4 concentrations (0.0, 7.5, 10.0 and 15%) with 50 % RDF, to study the effect of sea weed extracts on productivity of maize grown under rainfed conditions. Application of either 7.5% K sap (56.17 q ha-1) or 5% G sap (54.29 q ha-1) along with 100% RDF enhanced the grain yield by 34 and 30% respectively than application of 100% RDF alone (41.92 q ha-1). Application of 7.5% either K sap or G sap along with 50% RDF produce similar grain yield (38.42 and 38.83 q ha-1 respectively) as that with 100% RDF alone and thereby saving 50% fertilizer need of the crop.Application of either 7.5% K sap or 5% G sap with 100% RDF not only increased the grain yield but also increased the nutrient uptake as well as improved soil fertility after crop harvest for sustainable crop production.